Communication Pattern between Musculocutaneous and Median Nerve in Arm: A Cadaveric Study (Nepal Medical College Journal, 2025)
The brachial plexus is a major nerve network that supplies upper limb. Musculocutaneous nerve (MCN) and median nerve (MN) are two of the branches of cords of brachial plexus which may communicate resulting in the most common variation of the plexus. Recognition and knowledge of such possible anatomical variation will be helpful in the field of neurology, anesthesia and surgery. This study aims to determine the incidence of communication pattern between MCN and MN. Formalin fixed, 50 cadaveric upper limbs of both sides available in the Department of Anatomy were dissected over a period of one year from August 2024 – July 2025. The brachial plexus, MCN and MN were exposed carefully. If Communication was present between MCN and MN, it was classified with reference to Le Minor classification. Variation that does not relate with Le Minor classification was presented as other pattern. The communication between MCN and MN were found in 13 upper limbs (26.0%) and in remaining 37 upper limbs (74.0%) it was absent. Regarding classification of the communication patterns, distribution were found to be; Type I in 37 (74.0%), Type II in 8 (16.0%), Type V in two (4.0%) and other types in three (6.0%) upper limbs (Le Minor classification). MCN communicates with MN after piercing through the coracobrachialis muscle in eight of the upper limbs (Type II). While in two specimen, the communication was present before piercing the coracobrachialis muscle, grouped as other type. MCN was completely absent in two of the upper limbs (Type V).